Efektivitas Pendekatan Jelajah Alam Sekitar Dengan Model Group Investigation Pada Materi Atmosfer Kelas X IPS SMA N 1 Bawang Tahun Pelajaran 2016/2017 - Hanifah, Utik Milati; Tukidi, Tukidi; Sriyanto, Sriyanto (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2018)
This study is aiming to identify the effectiveness of natural roaming approach by using group investigation model on atmospheric materials in class X SMA N 1 Bawang. The criteria of effectiveness in this research are: 1) the ability of teacher in managing learning; 2)the mastery of students learning outcomes classically; 3) an achievement of students activity ; 4) students’ positive responses to the learning system. Design of this research is a pre-experimental study which had been conducted in SMA N 1 Bawang with the subject of class X IPS 3 which consists of 32 students. The result of the study shows that the teacher’s ability in managing the learning reach out 76,14 % , and it includes into good category. The mastery of classically students learning outcomes reach out 56.25%, so this criterion has not been fulfilled. Students’ activity in learning reach out 71.88%, and it includes into high category. Whereas the students’ response in adhering the learning reach out 97.66%, it includes into good category. Therefore, it could be concluded that Natural Roaming approach has not been effective applied in geography subject learning in atmospheric material for class X SMA N 1 Bawang 2016/2017 year school. Penelitian ini bertujuan untuk mengetahui efektivitas pendekatan jelajah alam sekitar dengan model group investigation pada materi atmosfer kelas X SMA N 1 Bawang. Kriteria efektivitas dalam penelitian ini adalah : 1) kemampuan guru dalam mengelola pembelajaran, 2) ketuntasan hasil belajar siswa secara klasikal, 3) ketercapaian aktivitas siswa, dan 4) tanggapan positif siswa terhadap pembelajaran. Desain penelitian ini adalah penelitian pre-eksperimen yang dilakukan di SMA N 1 Bawang dengan subjek kelas X IPS 3 yang berjumlah 32 siswa. Hasil penelitian menunjukkan bahwa kemampuan guru mengelola pembelajaran mencapai 76,14% dan masuk dalam kategori baik. Ketuntasan hasil belajar siswa secara klasikal mencapai 56,25% sehingga pada kriteria ini belum terpenuhi. Aktivitas siswa dalam pembelajaran mencapai 71,88% dan masuk dalam kategori tinggi. Sedangkan respon/tanggapan siswa dalam mengikuti pembelajaran mencapai 97,66% masuk dalam kategori baik. Dapat disimpulkan bahwa pendekatan jelajah alam sekitar belum efektif dalam pembelajaran geografi materi atmosfer kelas X di SMA N 1 Bawang tahun pelajaran 2016/2017.